Fuzzy time series dalam meramalkan jumlah produksi karet di Sumatra Utara - Arika, Arika; Daratullaila, Daratullaila; Sirait, Khairunnas Fadjriah; Sari, Riezky Purnama (Majalah Ilmiah Matematika dan Statistika, 2024)
Rubber (Hevea brasiliensis) belongs to the genus Heveadari familia Euphorbiaceae which is a tropical woody tree native to the amazon jungle. Rubber is one of the plantation crops that is very important for the economy in Indonesia. Rubber production in North Sumatra has increased every year. To find out whether the amount of rubber production in North Sumatra increases or decreases next year by forecasting the amount of rubber production and getting better forecasting results in the future. This estimate can use the fuzzy time series forecasting method. The fuzzy time series uses the fuzzy set theory as the basis for calculations and a concept used to forecast actual data formed with linguistic variables. The method used in predicting the amount of rubber production in North Sumatra is the fuzzy time series method with data from 1997 to 2021. And the result of forecasting rubber production in 2022 is 261997 with MAPE of 0.54%. Keywords: Forecasting, rubber production, fuzzy time seriesMSC2020: 62M10, 62M20, 62M86, 03E72